Accessing Higher Education through Open and Distance Learning by People with Disabilities in Nigeria - Ihuoma, Chinwe Patience; Abaa, Angela Ebere (West African Journal of Open and Flexible Learning, 2022)
Disability means any form of physical or mental condition that restricts a person’s way of life. It ranges from visual impairments, lameness to complex intellectual or mental health challenges. Research reveals that about 15% of the world’s population suffer from various forms of disabilities. The number is expected to keep increasing because of the fact of continuing conflicts, terrorism, hunger and aging populations, . People with disabilities are usually discriminated against in virtually everything, including education and employment. This tends to lead to a vicious cycle of more poverty, further exclusion and discrimination. However, the plight of people with disability was captured by the United Nations and provisions were made for them in the Sustainable Development Goals (SDGs). SDG 4 stipulates for the provision of inclusive, equitable and quality education for all by 2030, as well as for lifelong learning. Two of the targets of SDG 4 include the elimination of discrimination against people with disabilities and the provision of infrastructure and materials for improved access to education for all. Since education is a sure way of overcoming poverty and discrimination, the question becomes how to include more people with disabilities into institutions of higher learning? This paper therefore reviewed ways of making Open and Distance Education (ODE) more accessible to People with Disabilities (PWD). PWDs have problems with enrolment, physical environment, support services, finances, among others. Recommendations were made as to how to ameliorate these problems and have more people with disabilities accessing and succeeding in Open and Distance Education.
Keywords: Access; Higher Education; Disability; Open and Distance Education